2017
DOI: 10.1371/journal.pone.0187861
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effectiveness of a video-based contact intervention in improving attitudes of Penang primary care nurses towards people with mental illness

Abstract: BackgroundMental illness-related stigma is common, and is associated with poorer outcomes in people with mental illness. This study evaluated the attitudes of primary care nurses towards people with mental illness and its associated factors; and the effectiveness of a short video-based contact intervention (VBCI) in improving these attitudes using a Malay version of the 15-item Opening Minds Stigma Scale for Healthcare Providers (OMS-HC-15-M).MethodsA 5-minute VBCI was developed comprising elements of psychoed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 78 publications
1
43
0
1
Order By: Relevance
“…Contrary to these, findings of two experimental studies revealed that interventions on mental illness were predictive of positive outcomes in anti‐stigma programs (Fernandez et al, 2016; Y. P. Ng et al, 2017). Furthermore, clinical posting in psychiatry was shown to increase positive attitudes towards mental health issues and psychiatry among female students (Reddy et al, 2005).…”
Section: Resultsmentioning
confidence: 92%
“…Contrary to these, findings of two experimental studies revealed that interventions on mental illness were predictive of positive outcomes in anti‐stigma programs (Fernandez et al, 2016; Y. P. Ng et al, 2017). Furthermore, clinical posting in psychiatry was shown to increase positive attitudes towards mental health issues and psychiatry among female students (Reddy et al, 2005).…”
Section: Resultsmentioning
confidence: 92%
“…According to Evans-Lacko and Knapp [10], cultural contexts in which mental illness is stigmatized may prevent an employee from disclosing their mental illness status and take sick-leave due to mental health-related reasons. This is the case in Malaysia, where even though as high as one thirds of Malaysians were reported as suffering from a mental illness [78], there is still a lack of knowledge and a prevalence of stigma against individuals who are mentally ill or suicidal [7981].…”
Section: Discussionmentioning
confidence: 99%
“…; Ng et al . ), yet it has been described as the most effective method to do so (Corrigan ; Thornicroft et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, not every type of contact is useful to reduce stigma (Eisenberg et al 2012;Ng et al 2017), yet it has been described as the most effective method to do so (Corrigan 2012;Thornicroft et al 2016). In fact, mental health professionals, despite continued relation with people with psychiatric diagnoses, still maintain stigmatizing attitudes (Hansson et al 2013;Schulze 2007).…”
Section: Discussionmentioning
confidence: 99%